Mental health and social support - Islam, Md Nurul; Iqbal, Kazi Ferdous (Chittagong University Journal of Biological Sciences, 2013)
The present study was undertaken to investigate the effect of social support on mental health. A total of 100 adult respondents (50 normal, 50 mental patients) of age ranging from 18 to 45 were selected as the sample of the study. The Bangla version of Social Support Scale & Mental Health Questionnaire or GHQ-12 was used in the study. Three aspects of social support were measured: number of social support (SSN), importance of social support (SSI) and satisfaction of social support (SSS). Results of the present study indicated that normal and mental patients differed significantly from each other in terms of social support. This means that the more the social support the better was the respondents mental health. The result also indicated that normal people had the better mental health than mental patients. Gender had no significant effect on normal & mental patients. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13410 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):95-107, 2008